(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence and factors associated with herbal medicine use among hypertensive outpatients at Nguyen Tri Phuong Hospital. Subjects and methods: A cross-sectional study was conducted among 590 hypertensive outpatients from March to May 2025. Data were collected through face-to-face interviews using a structured questionnaire. Results: Among the 590 participants, 38.1% reported using herbal medicine within the past 12 months; however, only 8.9% used it for the treatment or prevention of hypertension. Most participants did not disclose their herbal use to healthcare professionals. Multivariable analysis showed that females (AOR: 2.14; 95% CI: 1.559-4.053) and smokers (AOR: 3.222; 95% CI: 1.564-6.638) were more likely to use herbal medicine. Compared with the retired group, homemakers (AOR: 0.305; 95% CI: 0.178-0.523) and other occupations (AOR: 0.338; 95% CI: 0.193-0.591) were less likely to use herbal medicine. Conclusion: The study has shown that the use of herbal medicines is quite prevalent among patients with hypertension. Therefore, it is necessary to strengthen management efforts and integrate routine screening into clinical practice.